Pharmacological treatment of schizophrenia with comorbid substance use disorder. (22nd January 2016) - Azorin, Jean-Michel; Simon, Nicolas; Adida, Marc; Belzeaux, Raoul
ABSTRACT: Introduction : While antipsychotics remain the cornerstone of treatment for schizophrenic patients with comorbid substance use disorder (SUD), such treatment is nonetheless complicated by frequent medical comorbidity and poor adherence to medication.Areas covered : Randomised controlled trials (RCTs) on the efficacy of antipsychotics for the treatment of schizophrenic patients with comorbid SUD are reviewed and analysed on the basis of a systematic literature search (PubMed) ranging from 1985 to 2015. On the same basis, findings from RCTs on the efficacy of psychotropic and other medications used for primary SUD are summarised, and the main issues liable to influence treatment choice are discussed, including pharmacodynamic as well as pharmacokinetic interactions, adherence, medical comorbidity and the impact on brain structure.Expert opinion : As far as the treatment of schizophrenic patients with SUD is concerned, direct and indirect evidence tends to stand in favour of the use of second-generation antipsychotics (SGAs), and particularly those with lower metabolic, cardiovascular and extrapyramidal side effects, as well as those with a depot formulation. A few of the usual medications for the treatment of primary SUD, such as naltrexone and disulfiram for alcohol use and bupropion for tobacco cessation, can also be safely and efficiently administered to schizophrenic patients with SUD.